The effects of computer-mediated synchronous and asynchronous direct corrective feedback on writing: a case study. Issue 3 (2nd April 2016) - Shintani, Natsuko
Abstract : This case study investigated the characteristics of computer-mediated synchronous corrective feedback (SCF, provided while students wrote) and asynchronous corrective feedback (ACF, provided after students had finished writing) in an EFL writing task. The task, designed to elicit the use of the hypothetical conditional, was completed by two Japanese university students in either the SCF or ACF condition. The writing process was video-recorded using the screen-capture function. An interview involving stimulated recall was conducted immediately after the writing session to investigate the two writers' perceptions about the feedback they received. The main findings were that (1) SCF created an interactive writing process similar in some respects to oral corrective feedback; (2) both the SCF and ACF promoted noticing-the-gap, but self-correction was more successful in the SCF condition; (3) focus on meaning and form took place contiguously in the SCF condition while it occurred separately in the ACF condition; and (4) both types of feedback facilitated metalinguistic understanding of the target feature, reflecting the unique features of writing (i.e., its slow pace, its permanency and the need of accuracy). These differences were confirmed by analyzing compositions written by 15 similar learners who received either type of feedback.